The Development of LKPD Multimedia using Problem-Based Learning Model to Improve Critical Thinking Ability of Elementary School Students - Hasanah, Nurul; Purba, Azrina; Rajagukguk, Kiki Pratama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to improve students' critical thinking skills and instill a good understanding of learning concepts through the use of Multimedia Student Worksheets based on Problem Based Learning (PBL) Models. The LKPD that will be developed only contains the sub-themes of Temperature and Heat, this is due to the limitations of the researcher. The development model used in this study is the Dick & Carey development model which consists of 10 steps. The data obtained were analyzed descriptively and statistical tests using SPSS. To produce quality products, the development of LKPD in research uses criteria consisting of Relevance, Consistency, Practically and Effectively. The population used in this study were fifth grade students of SD Negeri Gebang-Langkat District. Based on the results of the study showed that (1) LKPD was declared very valid (86.87%) by validators, (93.3%) by teachers and (87.3%) by students in three different schools (2) Differences in critical thinking skills Significant students between classes using PBL Model-based Multimedia LKPD have an average score (86.27) while the LKPD available at school (43.63), where the significant t-test shows 0.000 <0.050 Ha is accepted.Â